Tropical Vacation for Paediatricians - Farquhar, J. W. (1974)
The purpose of two weeks spent in a developing country at relatively low cost (£145 each) was to have an enjoyable holiday while seeing something of the child health, culture, and economy of the country. Its deeper significance was to attract some participants to giving time and support to developing countries while making their teaching in Britain more relevant both to the native British student and to visitors from developing countries. There was no preaching. It was a “look, see, think” operation. Ghana was selected because of its friendliness, enthusiasm for the project, and helpful co-operation given in initial planning. The experience was judged successful by most and possibly by all. The friendly contacts established with very able Ghanaian colleagues may be mutually helpful in the field of medical education.